Pleural pressure theory revisited: a role for capillary equilibrium - Casha, Aaron R.; Caruana-Gauci, Roberto; Manche, Alexander; Gauci, Marilyn; Chetcuti, Stanley; Bertolaccini, Luca; Scarci, Marco (Journal of Thoracic Disease, 2017)
Background: Theories elucidating pleural pressures should explain all observations including the equal and opposite recoil of the chest wall and lungs, the less than expected pleural hydrostatic gradient and its variation at lobar margins, why pleural pressures are negative and how pleural fluid circulation functions. Methods: A theoretical model describing equilibrium between buoyancy, hydrostatic forces, and capillary forces is proposed. The capillary equilibrium model described depends on control of pleural fluid volume and protein content, powered by an active pleural pump. Results: The interaction between buoyancy forces, hydrostatic pressure and capillary pressure was calculated, and values for pleural thickness and pressure were determined using values for surface tension, contact angle, pleural fluid and lung densities found in the literature. Modelling can explain the issue of the differing hydrostatic vertical pleural pressure gradient at the lobar margins for buoyancy forces between the pleural fluid and the lung floating in the pleural fluid according to Archimedes’ hydrostatic paradox. The capillary equilibrium model satisfies all salient requirements for a pleural pressure model, with negative pressures maximal at the apex, equal and opposite forces in the lung and chest wall, and circulatory pump action. Conclusions: This model predicts that pleural effusions cannot occur in emphysema unless concomitant heart failure increases lung density. This model also explains how the non-confluence of the lung with the chest wall (e.g., lobar margins) makes the pleural pressure more negative, and why pleural pressures would be higher after an upper lobectomy compared to a lower lobectomy. Pathological changes in pleural fluid composition and lung density alter the equilibrium between capillarity and buoyancy hydrostatic pressure to promote pleural effusion formation.